Relationship between Honesty-Humility and Cyberbullying Perpetration: A Moderated Mediation Model - Geng, Jingyu (Journal of interpersonal violence, 2022)
Previous studies have verified the roles of big five personalities in cyberbullying perpetration (CP). The Big Five model has been revised to include an additional dimension, called Honesty-Humility (HH). It is not clear whether HH would be associated with CP. Thus, the effect of HH on CP was examined. To further explore this influencing mechanism, materialism was examined as a mediator, and parental psychological control (PPC) was examined as a moderator in the relationship between HH and CP. A total of 1,004 Chinese adolescents (M = 12.95, SD =1.12) participated in this study using a cross-sectional design and multiple questionnaires, namely, the Honesty-Humility subscale of the 24-item Brief HEXACO Inventory, the Revised Cyber Bullying Inventory, the Material Values Scale for Children, and the Parental Control Questionnaire. Correlation analyses indicated that CP, materialism, and PPC were significantly and positively correlated with each other, and were significantly and negatively associated with HH. The mediation model revealed that materialism played a mediating role in the relationship between HH and CP. The moderated mediation model revealed that stronger PPC strengthened the direct associations of HH with materialism and CP, and further strengthened the indirect relationship between HH and CP. Specifically, Chinese adolescents with lower levels of HH were more likely to build material values and further engaged in cyberbullying perpetration, when they perceived stronger PPC.